1989
DOI: 10.1111/j.1600-9657.1989.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a desensitizing dentifrice on dentinal hypersensitivity

Abstract: The objective of this study was to assess the effectiveness of a dentifrice with 2% dibasic sodium citrate in poloxamer 407 in decreasing dentinal hypersensitivity. The test toothpaste was compared with a control toothpaste containing 0.76% sodium monofluorophosphate in a 6-week double-blind clinical trial. A total of 75 hypersensitive teeth were examined in the test group, while 100 hypersensitive teeth were in the control group. Changes in hypersensitivity levels were monitored after 6 weeks, using thermal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…One disadvantage is that OTC desensitizing products may take up to 2-4 weeks to relieve symptoms whereas in theory a practitioner-applied therapy ideally may provide immediate relief of discomfort. although in some situations, pulpal extirpation or extraction of the offending tooth may be the treatment of choice (115). within 2 weeks) would, however, appear to be a significant advancement in the treatment of DH/RDS.…”
Section: Management Of Dh/rdsmentioning
confidence: 99%
“…One disadvantage is that OTC desensitizing products may take up to 2-4 weeks to relieve symptoms whereas in theory a practitioner-applied therapy ideally may provide immediate relief of discomfort. although in some situations, pulpal extirpation or extraction of the offending tooth may be the treatment of choice (115). within 2 weeks) would, however, appear to be a significant advancement in the treatment of DH/RDS.…”
Section: Management Of Dh/rdsmentioning
confidence: 99%
“…The exploratory SnF 2 toothpaste used in this study has been shown in clinical trials to reduce the severity of DH pain compared with conventional fluoride toothpaste in studies ranging from single brushing to 14 days' twice-daily brushing [22][23][24]. Similar formulations have shown benefits after 4 and 8 weeks of use [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study strengthen this theory, because viewing the dentine surface from above did not show any significant difference in the degree of occlusion from the SnF 2 containing toothpaste after 8 days of treatment. Clinical studies using the same toothpaste have shown it to provide relief from DH [22][23][24]. The model may therefore need to be further modified to include cross-sectional imaging of the tubules to identify occluding particles further down inside them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in Chap. Other miscellaneous treatment approaches have also been recommended, for example, occlusal adjustment associated with cervical abfraction lesion (Coleman et al 2003 ), crown restorations, root coverage surgery, pulp extirpation, extraction (Ong and Strahan 1989 ), homoeopathic remedies (Plantago) ( www.hpathy.com ), propolis (Mahmound et al 1999 ) and hypnosis Eitner et al 2010 ). Examples of these products are resins, varnishes, primers, dentine bonding agents and glass ionomer cements which contain fl uoride, aluminium, potassium or ferric oxalates; silica or calcium-containing materials; and protein precipitants to decrease dentin permeability or block the fl uid movement through dentin (Tables 5.3 and 5.4 ).…”
Section: Restorative Approachesmentioning
confidence: 99%